2005
DOI: 10.1097/01.fpc.0000175598.42141.59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thymidylate synthase gene polymorphisms on the survival of colorectal cancer patients receiving adjuvant 5-fluorouracil

Abstract: The present study aimed to prospectively investigate the influence of thymidylate synthase (TS) polymorphisms (5'-TSER, 3'-TSUTR) on the disease-free survival (DFS) and overall survival (OS) of patients with colorectal cancer (CRC) who were treated with adjuvant 5-fluorouracil (5-FU) therapy. Patients were followed up for 19+/-14 months (median+/-SD). TS genotypes were determined from the peripheral blood mononuclear cells of 166 patients by polymerase chain reaction-polyacrylamide gel electrophoresis and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 26 publications
4
48
2
Order By: Relevance
“…The TS gene is located in chromosome 18p11.32, and a tandem repeat polymorphism has been identified in the 5'-untranslated region (UTR) enhancer region of the TS promoter (TSER, rs34743033). TSER is located immediately upstream of the ATG codon initiation start site, which contains triple (TSER 3R) or double (TSER 2R) repeats of 28-bp sequences (Hitre et al, 2005). In vitro and in vivo studies have shown that TS expression is TSER-genotype dependent, and that the 3R allele is associated with a higher TS expression level (Kawakami et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The TS gene is located in chromosome 18p11.32, and a tandem repeat polymorphism has been identified in the 5'-untranslated region (UTR) enhancer region of the TS promoter (TSER, rs34743033). TSER is located immediately upstream of the ATG codon initiation start site, which contains triple (TSER 3R) or double (TSER 2R) repeats of 28-bp sequences (Hitre et al, 2005). In vitro and in vivo studies have shown that TS expression is TSER-genotype dependent, and that the 3R allele is associated with a higher TS expression level (Kawakami et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer (CRC) patients, the combination of 5 0 UTR and 3 0 UTR TYMS polymorphisms could discriminate between high and low responders in terms of improved DFS, with better survival in individuals carrying the low-expressing alleles. 5,6 However, an opposite trend has been reported by Jakobsen et al 7 Differences reported among studies could be due to several factors including genotyped tissues (healthy or tumor), which employed a different method of drug administration and a different treatment setting (metastatic disease vs adjuvant therapy). In any case, it is likely that a single polymorphism of TYMS is not sufficient to explain changes in the clinical benefit of 5-FU, and complex combinations of variants should be considered.…”
mentioning
confidence: 61%
“…However, the results are conflicting and there is no consensus on the clinical value of these variants [9][10][11]. For instance, while some studies report association between a favorable clinical response and variants at the 5′UTR and 3′UTR regulatory regions of the TYMS gene, other reports have failed to replicate such results [12][13][14][15][16]. None of these studies was performed on the Latin-American populations and studies in this group may contribute to the understanding of the biological significance of TYMS variants and their pharmacological relevance for CRC patients undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 69%